Emergency Department Comprehensive Social Risk Screening and Resource Referral Program - Kaytlena Stillman; Alex Dahut; Antonina Caudill; Katie Hren; Krystal Green; Marie Lauzon; Susan Jackman; Alexander Lawton; Tananshi Chopra; Joel Geiderman; Sam Torbati (Western Journal of Emergency Medicine)
Introduction: The emergency department (ED) is an appropriate location to screen for and address social risks among patients; however, a standardized process does not currently exist. Our objective in this study was to describe the implementation and findings of a social risk screening and resource referral program using a comprehensive screening questionnaire. Methods: We conducted a prospective, cohort study between July 2022–April 2023 at a single academic, urban ED in Los Angeles, CA. Trained staff on rotating shifts recruited ED patients between 6 am to midnight, with an average of 40 hours of coverage per week including weekends. Patients were excluded if they were <18 years of age, could not provide informed consent, or were deemed too medically unstable. Trained staff screened eligible consenting patients at ED bedside for social risks within 12 different domains of social determinants of health using a 19-question survey. Personalized resources were provided through an online platform or through direct communication with a social worker. Demographic data and patient responses were recorded in a deidentified database. We used a univariate logistic regression analysis to evaluate associations between demographic information and burden of social risk. Results: A total of 4,277 ED patients were considered for screening, and 1,677 (39.2%) were eligible: 1,473 (87.8%) patients consented to social risk screening, and 1,078 (73.2%) of them had at least one social risk as indicated by the screening questionnaire. The most commonly reported social risks were social isolation (39%) and depression (23%). Between 88.9–96.8% of patients categorized as medium social risk were successfully provided resources through the online platform. Between 80.8–100% of patients categorized into high social risk had successfully connected with a social worker while in the ED. In this sample, there were significantly higher odds of having greater than one social risk for female (odds ratio [OR] 1.30, 95% confidence interval [CI] 1.02–1.67) and Black patients (OR 1.37, 95% CI 1.02–1.85) compared to male and White patients, respectively. Conclusion: This study describes the findings from a comprehensive social risk screening and resource referral program at a large, urban, academic ED. The results will inform resource prioritization at the study institution. This model can serve as a basis for similar institutions to use, while individualizing their own approach.